2017
DOI: 10.1111/cid.12498
|View full text |Cite
|
Sign up to set email alerts
|

Anterior single implants with different neck designs: 5 Year results of a randomized clinical trial

Abstract: For anterior single tooth replacements, scalloped implants show less favorable radiographic and clinical outcome compared to regular implants with a smooth neck or rough neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(52 citation statements)
references
References 24 publications
0
52
0
Order By: Relevance
“…Some studies reported a high mean bone loss despite lower percentages of bleeding on probing. den Hartog, Meijer, Vissink and Raghoebar (2017) reported a mean bone loss of 2.3 mm after a follow‐up of 5‐year with a corresponding 87.5% BoP. Arnhart et al.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies reported a high mean bone loss despite lower percentages of bleeding on probing. den Hartog, Meijer, Vissink and Raghoebar (2017) reported a mean bone loss of 2.3 mm after a follow‐up of 5‐year with a corresponding 87.5% BoP. Arnhart et al.…”
Section: Resultsmentioning
confidence: 98%
“…den Hartog et al. (2017) reported the highest mean PPD (4.3 mm) and a reported prevalence of peri‐implantitis of 11.5%. Mean BoP showed a strong correlation with peri‐implantitis (Pearson r  = 0.45).…”
Section: Resultsmentioning
confidence: 99%
“…In scalloped implants, marginal bone level changes from surgery to 1 year was 1.36 mm ( N = 2 studies, 95% CI: [0.72, 2.00], p < 0.001) higher than that of cylindrical implants (post hoc power analysis >95%). The 5‐year report of den Hartog et al () confirms the maintenance of the difference between scalloped and flat implants, with 44% of the scalloped implants presenting bone loss >2 mm.…”
Section: Resultsmentioning
confidence: 87%
“…Thirty‐four studies addressed two‐piece bone level implants, with a total of 2,421 implants at baseline and 2,080 implants at the final follow‐up. Eleven studies compared machined collar implants with rough collar implants (Alsabeeha, Payne, Silva, & Thomson, ; Hsu et al, ; Jacobs et al, ; Kim, Lee, Lee, & Yi, ; Ravald et al, ; Vroom et al, ) and with rough collar implants with microthreads or microgrooves in the coronal portion (den Hartog, Meijer, Vissink, & Raghoebar, ; Hof et al, ; Nickenig et al, ; Penarrocha‐Diago et al, ; Shin et al, ). All studies presented conventional loading protocols (superior to 2 months of osseointegration) except for the work of Alsabeeha et al, with early loading at 6 weeks, and the work of Kim et al () with immediate loading.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation